Stardust Pattern As Evolution Of Pigmented Spitz Nevi During Childhood - Brunetti, Bruno; Briatico, Giulia; Scharf, Camila; Cabo, Horacio; Scalvenzi, Massimiliano; Barbato, Filomena; Savoia, Francesco; Thomas, Luc; Argenziano, Giuseppe; Brancaccio, Gabriella (Dermatology Practical & Conceptual, 2023)
Introduction: Spitz nevi (SN) are benign melanocytic proliferations frequently occurring in children. Some pigmented SN with starburst pattern evolve into the “stardust” one, which is characterized by a central, black to gray, hyperpigmented area and remnants of a brown network at the periphery. These dermoscopy changes are often the first alert to induce excision.Objectives: The aim of this study is to enlarge the case series of stardust SN in children, in order to increase confidence with this new dermoscopic pattern and reduce unnecessary excisions.Methods: This retrospective observational study was conducted with SN cases received from IDS members. The inclusion criteria were: clinical and/or histopathologic diagnosis of Spitz naevus with starburst appearance in children <12 years old, availability of a dermoscopic image at baseline and after follow-up of at least 1 year, availability of patient’ data. The dermoscopic images and their changes over time were assessed by three evaluators in consensus.Results: 38 SN were enrolled, with median age of 7 years and median FUP duration of 15,5 months. Comparing the evolution with time of FUP, no significant differences were found between growing and involuting lesions in terms of patient age and sex, location and palpability of lesions. Conclusions: The long follow up reported in our study could really support the concept of benignity of changing SN. A conservative approach is acceptable for nevi showing the stardust pattern, because it may be considered a physiological evolution of pigmented Spitz nevus, and urgent surgeries could be avoided.